(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Tinnitus (lat. tinnīre - "to ring like a bell") is a sensation of ringing or ringing in the ears. Often, people describe noise as a high-frequency sound. According to various data, from five to eight percent of the world’s population lives with this disease. Tinnitus is generally considered to be characteristic of the elderly. Nevertheless, this problem is often observed in young people. This is related to visiting noisy places, as well as listening to loud music through headphones.